Radiotherapy-Resistant Pediatric Bladder Rhabdomyosarcoma: A Case Report - Dhamiyati, Wigati; Dwidanarti, Sri Retna; Kurniawan, Torana; Ekaputra, Ericko; Mediana, Lidya; Yanuarta, Seize Edwiena (Radioterapi & Onkologi Indonesia, 2023)
AbstractIntroduction : Rhabdomyosarcoma (RMS) is a type of malignancy that is relatively rare and originates from soft tissue. RMS can appear at any age but is most common in children and toddlers. Rhabdomyosarcoma managed use chemotherapy as the main modality, followed by surgery or radiation if there was residual or recurrence.Case Presentation : In this report, the author will review a case of radioresponsiveness pediatric bladder rhabdomyosarcomaThe patient received chemotherapy with cyclophosphamide-mesna, vincristine, and actinomycin. After chemotherapy, the mass was reduced partially and then followed by whole bladder external radiation.Conclusions : Rhabdomyosarcoma in the child's bladder may exhibit radioresistance characteristics Keywords : rhabdomyosarcoma, radiation, pediatric, bladder